Analisis Kajian Sintaksis pada Buku Bahasa Indonesia Jenjang SD Kelas Bawah Terbitan Kemdikbudristek - Viona Nurafiani; Apriyanti, Dwi Norma; Nuryani, Nuryani (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Syntax material has been introduced when we enter elementary school, in Indonesian language lessons, especially at the lower grade elementary school level, they have learned grammar based on their level of understanding and ability. This is seen in their textbooks that have been analyzed. The purpose of this study is to describe Indonesian language materials related to syntax in lower grade elementary school textbooks. The method used in this research is descriptive qualitative approach, with data collection technique in the form of simak catat. The data source in this research is a lower grade elementary school textbook published by Kemendikbudristek. The results showed that in grade 1 students began to recognize material about words and sentences, in grade 2 students had material about sentence functions, active and passive sentences. Then in grade 3 there is material on prohibition sentences, suggestion sentences and question words.